Synthesis of three-arm block copolymer poly(lactic-co-glycolic acid)–poly(ethylene glycol) with oxalyl chloride and its application in hydrophobic drug delivery - Zhu, Xiaowei (Int J Nanomedicine, 2016)
PURPOSE: Synthesis of star-shaped block copolymer with oxalyl chloride and preparation of micelles to assess the prospect for drug-carrier applications. MATERIALS AND METHODS: Three-arm star block copolymers of poly(lactic-co-glycolic acid) (3S-PLGA)–polyethylene glycol (PEG) were synthesized by ring-opening polymerization, then PEG as the hydrophilic block was linked to the terminal hydroxyl of 3S-PLGA with oxalyl chloride. Fourier-transform infrared (FT-IR) spectroscopy, gel-permeation chromatography (GPC), hydrogen nuclear magnetic resonance ((1)H-NMR) spectra, and differential scanning calorimetry were employed to identify the structure and properties of 3S-PLGA-PEG. Rapamycin (RPM)-loaded micelles were prepared by solvent evaporation, and pyrene was used as the fluorescence probe to detect the critical micelle concentration of the copolymer. The particle size, distribution, and ζ-potential of the micelles were determined by dynamic light scattering, and the morphology of the RPM-loaded micelles was analyzed by transmission electron microscopy. High-performance liquid chromatography was conducted to analyze encapsulation efficiency and drug-loading capacity, as well as the release behavior of RPM-loaded micelles. The biocompatibility of material and the cytostatic effect of RPM-loaded micelles were investigated by Cell Counting Kit 8 assay. RESULTS: FT-IR, GPC, and (1)H-NMR suggested that 3S-PLGA-PEG was successfully synthesized. The RPM-loaded micelles prepared with the 3S-PLGA-PEG possessed good properties. The micelles had good average diameter and encapsulation efficiency. For in vitro release, RPM was released slowly from 3S-PLGA-PEG micelles, showing that 3S-PLGA-PEG-RPM exhibited a better and longer antiproliferative effect than free RPM. CONCLUSION: In this study, we first used oxalyl chloride as the linker to synthesize 3S-PLGA-PEG successfully, and compared with reported literature, this method shortened the reaction procedure and improved the reaction yield. The micelles prepared with this material proved suitable for drug-carrier application.